Peningkatan Pengetahuan Melalui Pemberdayaan Kader dan Tokoh Masyarakat Dalam Sosialisasi Dampak Stunting Terhadap Tumbuh Kembang Anak Serta Pencegahannya - Imas Yoyoh (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Stunting is a condition where children under five years of age fail to thrive due to chronic malnutrition, resulting in height not matching their age. Stunting increases the risk of cognitive and developmental disorders in children. Indonesia is included in the group with a high prevalence of stunting cases which is the responsibility of all stakeholders, families, health institutions, government and society. Community empowerment through health promotion by increasing health knowledge and behavior is one of the efforts to reduce stunting. The participation of posyandu cadres and parents is needed in carrying out stunting screening. To realize an active role in reducing stunting, community service is being held through health promotion and education regarding the socialization of stunting and its impact on children's growth and development as well as its prevention for the community of Periuk Jaya sub-district, Tangerang City. The aim of the activity is to assist the government program in reducing stunting. The activity method is carried out through observation, socialization, holding seminars and evaluation. Activity results: Participants who attended included posyandu cadres, parents with toddlers, pregnant women, as well as 30 RT, RW and sub-district level governments. Then the results of the post test showed that participants had increased their knowledge, so that they could indirectly change people's behavior in reducing and screening for stunting independently. Participants are also able to demonstrate simulated skills related to the material presented. Suggestions for cadres who have attended the seminar can transfer their knowledge to other posyandu cadres and the wider community. Community figures who have the power to play a role in decision making can advocate for active participation in socialization and health promotion for prospective brides, teenagers and husbands.